Benefits of acknowledging global divestments in organizational data retention : Case: Neste - Klimoff, Jussi (My University, 2023)
Divestment, the act of separating or selling a business unit, is a complex process involving a lot of internal and external variables. Nowadays when data is becoming an increasingly important asset for organizations, it is also increasingly in the center stage in divestment projects. Many divestment projects involve the separation of relevant IT systems and business unit data, which can be a complex process on its own right, consuming both time and money. This emphasizes the importance of successful data migration, the process of handing the data over to the acquirer. In the context of this study, defining what data should be given to the acquirer has previously been causing challenges, data may have been hard to locate, or the amount of historical data has been so abundant that is has caused unwanted strain on migration execution. This study explores the opportunity to utilize data retention to simplify the data definition process and improve divestment project efficiency, which today is in increasing demand. This topic combines research subjects that have so far been somewhat neglected in their respective research areas: divestment, data retention, and IT carve-out, the act of separating IT systems during divestments. Prior research on divestments has been mostly considering them as a subsection of M&A research. Most of the literature researching data retention has focused on the legislature and the individual’s perspective, neglecting the organizational perspective. The small amount of prior research on IT carve-outs likely stems from the small amount of divestment research altogether. Retention in divestment has been researched previously, but the focus has been on employee retention, not data retention. Here exists a research gap which this study aims to fulfil. This study was carried out as qualitative research. The report begins with a literature review, presenting the key concepts: divestment, data governance, and data retention. The theoretical data governance frameworks are adaptively utilized in the data analysis section and in the proposed action presentation. This research does not test any existing theory but uses existing frameworks as a support. The data collection method chosen for this study was expert interviews. Internal and external stakeholders who had prior experience from divestment projects were interviewed to properly understand divestment project variables, and what factors have previously caused challenges in divestment projects. The findings of this study support the further implementation of data retention principles into divestment related activities. Divestment subject matter experts were generally in favor of bolstering data retention, which would lead to more simplified data migration process, more streamlined divestment project with cost and time savings, and better data quality on the organizational level. This research was also basis for discussion regarding other plausible development projects regarding the use and enforcement of data retention.

Divestointi, eli liiketoimintayksikön myyminen tai erottaminen omaksi kokonaisuudekseen, on monimutkainen prosessi, johon liittyy paljon sisäisiä ja ulkoisia muuttujia. Data on nykypäivänä yhä tärkeämpi omaisuuserä yrityksille, ja sen rooli divestointiprojekteissa on myös keskeinen. Moniin divestointiprojekteihin kuuluu IT järjestelmien ja liiketoimintayksikön datan erottaminen irralleen muusta organisaatiosta. Tämä voi olla aikaa ja rahaa vievä prosessi. Tästä syystä onnistuneen datamigraation merkitys korostuu. Datamigraatiossa tiedot luovutetaan eteenpäin kaupan ostajaosapuolelle. Aikaisemmin datan määrittely – mitä dataa luovutetaan eteenpäin, on aiheuttanut haasteita. Datan paikantaminen on voinut olla vaikeaa tai historiallisen datan määrä niin suuri, että se on aiheuttanut ylimääräistä kuormaa migraation toteuttamiselle. Tämä tutkielma tarkastelee mahdollisuutta hyödyntää tietojensäilyttämiskäytäntöä (engl. data retention policy) datamigraation yksinkertaistamiseksi ja divestointiprojektin tehokkuuden parantamiseksi. Tutkielma tuo yhteen aiheita, jotka ovat aikaisemmassa tieteellisessä kirjallisuudessa jääneet melko vähälle huomiolle: divestointi, tietojen säilyttäminen, IT erotusprosessi (IT carve-out). Aikaisempi kirjallisuus on käsitellyt divestointia lähinnä M&A tutkimuksen alalajina. Tietojen säilyttämistä käsittelevä kirjallisuus on tarkastellut asiaa pääasiassa yksilön ja lainsäädännön perspektiivistä, jättäen organisaationäkökulman vähemmälle huomiolle. IT erotusprosessia käsittelevän kirjallisuuden vähäisyys todennäköisesti juontaa juurensa divestointikirjallisuuden vähäiseen määrään. Säilyttämistä (engl. retention) divestoinnin yhteydessä on käsitelty tieteellisessä kirjallisuudessa aiemmin ainoastaan työntekijöiden säilyttämisen (engl. employee retention) näkökulmasta. Näistä lähtökohdista on havaittavissa selkeä tutkimusaukko, jota tämä tutkielma pyrkii osaltaan täyttämään. Tutkielma toteutettiin laadullisena tutkimuksena. Se alkaa kirjallisuuskatsauksella, jossa esitellään keskeiset käsitteet: divestointi, tiedonhallinta (engl. data governance), sekä tietojen säilyttäminen. Tietojenhallinnan teoreettisia viitekehyksiä sovelletaan data-analyysissä sekä ehdotettua toimenpidettä käsittelevässä luvussa. Tutkielma ei testaa mitään aikaisempaa teoriaa, vaan hyödyntää olemassa olevia viitekehyksiä tutkimuksen tukena. Tiedonkeräysmenetelmäksi valittiin asiantuntijahaastattelut. Haastatteluissa kuultiin sisäisiä ja ulkoisia sidosryhmän jäseniä, joilla oli aikaisempaa kokemusta divestointiprojekteista, jotta voitiin kunnolla ymmärtää divestoinneissa vallalla olevat muuttujat ja haasteita aiheuttaneet tekijät. Tämän tutkielman löydökset tukivat tietojen säilyttämisen aiempaa suuremman sisällytyksen osaksi divestointeja. Asiantuntijat suhtautuivat myönteisesti tietojen säilyttämisen tarkempaan hallintaan, sen johtaessa yksinkertaisempiin datamigraatioihin, virtaviivaisempiin divestointiprojekteihin, minkä avulla voidaan saavuttaa resurssisäästöjä, sekä taata koko organisaation tiedon laadun parantuminen. Tutkielman pohjalta on käyty myös keskusteluja muiden aiheeseen liittyvien kehitysprojektien osalta.
Keywords: data retention, divestment